CAPITAL STRUCTURE OF PROPERTY AND REAL ESTATE COMPANIES IN INDONESIA SHARIA STOCK INDEX: INFLUENCE OF PROFITABILITY, LIQUIDITY, AND ASSET STRUCTURE - Dharmawan, Nurrahma Arif; Takidah, Erika (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The era of globalization has created free and borderless business competition. Slow growth in the property and real estate sector underscores the importance of companies managing their capital structure well to ensure business continuity. The objectives of this research are to assess the influence of Profitability, Liquidity, and Asset Structure on the Capital Structure of companies within the property and real estate sectors listed on the Indonesia Sharia Stock Index (ISSI) on the Indonesia Stock Exchange between 2020 and 2022. Utilizing a quantitative approach, the research draws on secondary data from annual reports of 48 sampled companies. The analytical methods employed include multiple linear regression, prerequisite tests, classical assumption tests, and hypothesis testing. The research findings indicate that the profitability variable has a negative and insignificant effect on the capital structure. Meanwhile, the liquidity and asset structure variables negatively and significantly affect the capital structure.